2016
DOI: 10.1016/j.lithos.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

I-type granitoids associated with the early Paleozoic intracontinental orogenic collapse along pre-existing block boundary in South China

Abstract: The early Paleozoic Wuyi-Yunkai orogeny resulted in extensive magmatism in the Cathaysia and eastern Yangtze blocks, South China. Identifying the nature of related magmatism is essential for understanding the orogeny that remains enigmatic with regard to its tectonic setting and geodynamic driving force. The Zhangjiafang pluton (438 ± 3 Ma) in western Jiangxi province is composed of predominant granodiorite with abundant coeval mafic-intermediate microgranular enclaves (MMEs) (~433 ± 5 Ma). The granodiorite sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 76 publications
1
21
0
Order By: Relevance
“…Our samples of dacite (ca. 438 Ma), together with coeval mafic intrusions and I‐type granites (e.g., Huang, Yu, Li, Tong, & Chen, ; Y. J. Wang, Zhang, Fan, Zhang, & Zhang, ; Yao et al, ; Yu, Huang, He, & Li, ), indicate the development of an extensional setting in the SCB at ca. 440 Ma, during the Caledonian period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our samples of dacite (ca. 438 Ma), together with coeval mafic intrusions and I‐type granites (e.g., Huang, Yu, Li, Tong, & Chen, ; Y. J. Wang, Zhang, Fan, Zhang, & Zhang, ; Yao et al, ; Yu, Huang, He, & Li, ), indicate the development of an extensional setting in the SCB at ca. 440 Ma, during the Caledonian period.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that the Caledonian Orogen in the SCB (>460–415 Ma), also known as the Wuyi–Yunkai Orogen, was an intraplate orogenic event (e.g., Charvet et al, ; Faure et al, ; Z. X. Li et al, ; J. H. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ) rather than a continental or arc collisional event involving the closure of the proposed Huanan Ocean within the SCB (Guo et al, ; Hsü, ; Hsü et al, ). Models of crustal anatexis (L. Wang et al, ) and lithospheric delamination or orogenic collapse (Z. X. Li et al, ; Shu et al, ; Y. J. Wang, Zhang, et al, ; Yao et al, ; Yu et al, ) have been put forward to explain the Caledonian structural elements, metamorphism, and magmatism. The Caledonian metamorphic rocks exhibit decompressional clockwise P–T paths (e.g., Faure et al, ; Huang et al, ; Z. X. Li et al, ) and yield metamorphic ages that cluster at 460–423 Ma (Y. J. Wang et al, ; Y. J. Wang, Fan, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that the South China Sea closed before 820 Ma, with the intracontinental orogeny commencing in the Caledonian (Charvet, ; Li et al, ; Song, Shu, & Santosh, ; Wang, Zhang, Fan, Zhang, & Zhang, ; Yu, Huang, & He, ). However, we believe that the amalgamation between the Cathaysia and Yangtze blocks was completed during the Caledonian; the evidences are as follows.…”
Section: Geological Significancementioning
confidence: 99%
“…The Chencai Complex has been the subject of intensive research since the 1970s, and significant advances in understanding its age and origins have been achieved (Chen et al, 2018;Li, Lin, Li, He, & Ge, 2018;Sun et al, 2018;Xia, Xu, Niu, & Liu, 2018 (Charvet, 2013;Song, Shu, & Santosh, 2015;Wang, Zhang, Fan, Zhang, & Zhang, 2013;Yu, Huang, & He, 2016). However, we believe that the amalgamation between the Cathaysia and Yangtze blocks was completed during the Caledonian;…”
Section: Significance Of the Yangtze-cathaysia Amalgamationmentioning
confidence: 99%